IMPLEMENTASI AN TRIAN DENGAN MENGGUNAKAN ARRAY - Nelli Hindriani; Narwen .; Hazmira Yozza (Jurusan Matematika FMIPA Universitas Andalas Padang, 2014)
In a multiprogramming computer, the queues are a data set where additionof elements could only done on a tip on the back side is called rear and the elementshad done through the end of the front sides which is called front. Due the queue is adata set, then the appropriate data type for presenting the queue is to use the array.The advantage of using an array as a data type is ability to which can collect multipledata of the same type within a single variable, thus within making the program consistsfrom the several of similar types does not require a lot of variables. In a queues systemthere are some models of queues that may could be done include queuing model byshifting the position of the element to the previous element, the queues front modelswere occupied by a new element entered, the queue model in which the move is madeby random element, and a queuing model random element position.